The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1007/bf01101101
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of arginine vasotocin, prolactin, aldosterone and corticosterone during prolonged dehydration in the domestic flowl: effect of dietary NaCl

Abstract: Three groups of White Plymouth Rock laying hens were adapted to three levels of dietary NaCl: low-NaCl food with tap water (LOW), high-NaCl food (1% NaCl w/w added) with tap water (HT), and high-NaCl food with 0.5% NaCl for drinking (HS). The birds were subjected to water deprivation (dehydration) for 18 days. Blood sampling was done at 2-4 day intervals. Plasma concentrations of arginine vasotocin (AVT), prolactin (PRL), aldosterone (ALDO) and corticosterone (CS) were determined by radioimmunoassay. Plasma os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
21
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(30 citation statements)
references
References 50 publications
9
21
0
Order By: Relevance
“…These responses are similar to those of Plymouth Rock hens (Clauss et al, 1988). Plasma aldosterone of the Cornish hens was 181 _+ 27 pg/ml (n = 21), very similar to values in Plymouth Rock hens (Arnason et al, 1986;Clauss et al, 1988) on the same dietary scheme.…”
Section: Comparison Of Cornish and Plymouth Rock Henssupporting
confidence: 80%
See 1 more Smart Citation
“…These responses are similar to those of Plymouth Rock hens (Clauss et al, 1988). Plasma aldosterone of the Cornish hens was 181 _+ 27 pg/ml (n = 21), very similar to values in Plymouth Rock hens (Arnason et al, 1986;Clauss et al, 1988) on the same dietary scheme.…”
Section: Comparison Of Cornish and Plymouth Rock Henssupporting
confidence: 80%
“…They were fed a low-NaC1 diet, wheat and barley, and distilled water ad libitum for 14 days prior to experiments (Choshniak et al, 1977). After securing a blood sample for aldosterone analysis (Arnason et al, 1986), the birds were killed by neck dislocation. The lower intestine was quickly removed and the coprodeal epithelium dissected from its muscular layer and placed in 38~ oxygenated Ringer's (mmol/liter: 140 Na, 8 K, 1.3 Ca, 1 Mg, 139 CI, 1 SO 4, 8 PO4, and 15 glucose, pH 7.3).…”
Section: Methodsmentioning
confidence: 99%
“…The response of arginine vasotocin, prolactin, aldosterone, or corticosterone to water restriction could have provided insight into possible control of fuel selection during water restriction. However, this study did not differ substantially in terms of magnitude or duration of water restriction from many other studies that have thoroughly investigated the hormonal response to acute water restriction in birds at rest and during exercise (2,17,19,39). Corticosterone does affect fuel use in birds, and would be the likely hormone responsible for elevated lean mass catabolism.…”
Section: Discussionmentioning
confidence: 62%
“…As discussed previously (Thomas et al, 1980;Skadhauge et al, 1983;Arnason et al, 1986), the concentration of plasma aldosterone (PA) is high in low-NaC1 fed birds and decreased by resalination. The spironolactone dose in our study lowered PA level in one group of LS hens to about half the control values; in the second group with the higher spironolactone dosage, the PA level was below the limit of detection.…”
Section: Endogenous Aldosterone Levelmentioning
confidence: 85%
“…Recent investigators compared the different time-course of aldosterone injections (Thomas et al, 1980;Clauss et al, 1984) with the time-course of NaC1 depletion or restoration (Thomas & Skadhauge, 1979Skadhauge et al, 1983;Clauss et al, 1984). All these studies indicated a time-dependent dietary stimulation of Na transport, and that in spite of already augmented plasma aldosterone levels after two days (Arnason et al, 1986) 'it takes several days for the epithelium to achieve its maximal transport rate. Acute aldosterone injections do not stimulate Na transport to Current-voltage relations are determined before and after the addition of amiloride (as indicated by the arrows).…”
Section: Introductionmentioning
confidence: 95%